Impact of the 2004 tsunami on household water treatment practices by the population of affected areas in Sri Lanka - Goonewardene, Nalayini Ponnambalam; Shipin, Oleg V.; Thamarat Koottatep; Vilas Nitivattananon; Joint Japan/World Bank Graduate Scholarship Program (JJ /WBGSP); Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Following the 2004 tsunami in the Indian Ocean, a survey was carried out in 2008 among the affected people who were resident in temporary camps for at least two weeks, in 6 of the 12 tsunami-affected districts. The overall objective was to investigate the household water treatment practices used by people displaced by the 2004 tsunami in Sri Lanka, comparing the three phases (pre-tsunami, displacement and post-tsunami phase), with an emphasis on the displacement phase. The overall goal was to establish which types of HWT were promptly available and most commonly used by the communities in the emergency situation (displacement phase) and under normal conditions (pre- and post-tsunami phase). A total of 508 households consisting of 2,353 people were interviewed with a prepared matrix questionnaire. Statistical analysis was performed on 14 hypotheses using SPSS software version 16, and associations were made using Pearson{u2019}s chi-square test (at 95% confidence interval). The study showed a very significant association (p< 0.0001) between the practice of HWT and tsunami phases. Similarly, the types of HWT (eleven types) were very significantly associated (p<0.0001) with the tsunami phases. However, pre-tsunami and displacement phases featured no apparent association (p>0.05) between water source and type of HWT, as opposed to the post-tsunami phase, which featured a very significant association (p<0.0001) between these variables. Boiling was the most commonly used HWT in all three phases (ranging from68.8 to 81.2%). Several NGOs tried to introduce solar disinfection as an HWT intervention (14.2%) but unfortunately it had not been continued after the displacement period since the people had not thought of it as a measure beyond emergency response. Household level chlorination was only marginally practiced (0-2.4%). Bottled and piped water was almost always accepted as {u2018}good water{u2019} not requiring additional treatment. However {u2018}truck water{u2019} was generally treated with caution. Increase in the use of filters was observed in the post-tsunami phase, possibly attributable to their free distribution. The most important conclusion made is that boiling appears to be an acceptable and effective HWT intervention in Sri Lanka, a practice of which may be sufficient for preventing tsunami-related epidemics, particularly when concomitant with a well-developed public health infrastructure typical of the country. The conclusion is particularly significant in the light of the previously reported studies suggesting that boiling was not associated with an improved water quality, and therefore (boiling) may not be considered as a sufficient intervention equal to chlorination-based strategies to improve household stored drinking water quality in post-disaster situations.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Environmental Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2009
Keywords: Tsunamis -- Sri Lanka; Water-supply -- Sanitation -- Sri Lanka